ҚОРАҚАЛПОҒИСТОН ЎЗБЕКЛАРИНИНГ НИКОҲ ТЎЙИГА ТЕГИШЛИ АЙРИМ МАСАЛАЛАР - Сатимова, Н.Г. (SCIENCE and SOCIETY, 2021)
This article gives a brief information on weddings and engagement ceremonies. It covers the wedding of Uzbeks in Karakalpakstan and the pre-wedding gift ceremony.
Keywords: marriage; sovchi; matchmaking; wedding ceremony; shur patir